The role of nickel in mechanical performance and corrosion behaviour of nickel-aluminium bronze in 3.5 wt.% NaCl solution. (15th July 2018) - Yang, Fenfen; Kang, Huijun; Guo, Enyu; Li, Rengeng; Chen, Zongning; Zeng, Yanhua; Wang, Tongmin
Graphical abstract: Highlights: The microstructures of four NAB alloys are characterized by SEM and TEM. The added Ni suppresses the formation of β' phase and increases the amount of κ phase. The corrosion resistance and yield strength are improved via Ni addition. The corrosion mechanism is analysed based on the EIS results and surface morphology. Abstract: The mechanical properties and corrosion behaviour in 3.5 wt.% NaCl solution of as-cast nickel-aluminium bronze (NAB) alloys with four Ni contents were investigated. The increase in Ni content leads to more precipitated κ phases, therefore improving the yield strength and hardness of the NAB alloys. Ni addition was found to significantly suppress the formation of corrodible β' phase and increase the Ni concentration in α solid solution. The electrochemical impedance spectroscopic and static immersion tests showed that the increase in Ni content (4.5–10 wt.%) improved the corrosion resistance of the NAB alloys in 3.5 wt.% NaCl solution.